Physical activity, sleep duration, and perceived stress among undergraduate medical students attending a tertiary hospital of Gandaki Province, Nepal - Hamal, Sharadha; Sharma, Bimala; Banastola, Sanju; Shrestha, Prabin (Journal of Gandaki Medical College-Nepal, 2025)
Introduction: Physical activity and sleep duration play crucial roles in influencing the perceived stress levels among medical students. The study aimed to assess if sleep duration and physical activity influenced the level of perceived stress among undergraduate medical students in a tertiary hospital of Gandaki Province, Nepal.Methods: A cross-sectional research design was employed among 240 undergraduate medical students of Gandaki Medical College Teaching Hospital & Research Center from November to December 2023. A self-administered questionnaire was used to collect the information. Sleep duration, level of physical activity, and perceived stress were measured through the use of validated scales: the Pittsburgh Sleep Quality Index for sleep duration, the International Physical Activity Questionnaire (IPAQ) for physical activity levels, and the Perceived Stress Scale for stress. Descriptive statistics, bivariate and multivariate logistic regression analysis were used.Results: The study revealed that 79.2% of undergraduate medical students experienced stress. Those reporting insufficient sleep duration had 3.49 times higher odds of perceived stress (95% CI: 1.72-7.06) as compared to their respective reference groups, with statistical significance (p